Gamma Radiation Induced Intestinal Proteomic Modulation in Mice: A Two Dimensional Electrophoretic Analysis - Bajaj, Sania; Singh, Abhinav; Kalita, Bhargab; Yashavarddhan, M.H.; Ranjan, Rajiv; Farooqi, Humaira; Gupta, Manju Lata (Defence Life Science Journal, 2017)
Exposure to high doses of radiation causes serious injuries in gastrointestinal tract, by affecting biomolecules of the tissue. To demonstrate the modulation of intestinal proteome by ionising radiations, we analysed changes in protein expression in 9 Gy irradiated C57BL/6 mice at 24 h and 72 h by using two dimensional electrophoresis technique. A total of 19 protein spots with statistical significance (fold change>1.5 and P<0.05) were found to be differentially expressed. Of these 07 spots were identified by MALDI-TOF MS and peptide mass fingerprinting techniques which matched with the known proteins documented in the online database. These proteins belong to biological-functional categories like cytoskeleton system, molecular chaperones, DNA damage response, and stress response. These identified radiation induced proteins can help in understanding the mechanisms behind the intestinal injuries and thus can become potential targets for therapeutics and also aid in drug development.